2015
DOI: 10.1155/2015/585917
|View full text |Cite
|
Sign up to set email alerts
|

Association between Genetic Variants and Diabetes Mellitus in Iranian Populations: A Systematic Review of Observational Studies

Abstract: Introduction. Diabetes mellitus as the most prevalent metabolic disease is a multifactorial disease which is influenced by environmental and genetic factors. In this systematic review, we assessed the association between genetic variants and diabetes/its complications in studies with Iranian populations. Methods. Google Scholar, PubMed, Scopus, and Persian web databases were systematically searched up to January 2014. The search terms were “gene,” “polymorphism,” “diabetes,” and “diabetic complications”; nephr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 87 publications
0
23
0
Order By: Relevance
“…Currently, there are about 415 million diabetics in the world, with more than 14 million in Brazil (3). In addition to the known environmental risk factors such as obesity, there are several genetic changes that are correlated to the pathophysiology of T2DM and its complications (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are about 415 million diabetics in the world, with more than 14 million in Brazil (3). In addition to the known environmental risk factors such as obesity, there are several genetic changes that are correlated to the pathophysiology of T2DM and its complications (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…In a meta-analysis study after pooling all the data of European, African, and Asian populations, it has been revealed that rs12255372 polymorphism of the TCF7L2 gene, significantly increases the risk of T2DM. In line with such findings, a positive association is observed between rs12255372 and rs7903146 variants of TCF7L2 gene and T2DM in Iranian population (54). Another study reported that 1082GG genotype of IL-10 and 174CC genotype of IL-6 are potential risk factors for T2DM in Egyptians (55).…”
Section: Genes Associated With Type 2 Diabetes In Non-asian Populationsmentioning
confidence: 60%
“…Several studies assessed the associations between GSTM1/GSTT1 null genotypes and DM risk but demonstrated conflicting results (53), while no significant association was found between GSTP1 and diabetes (51). Further, 1082A/G polymorphism of IL-10 seems to be a risk factor for T2DM in Asians, but not in Europeans or Africans (54). Among the candidate genes that are related to T2DM, the TCF7L2 exhibits one of the strongest genetic associations with diabetes.…”
Section: Genes Associated With Type 2 Diabetes In Non-asian Populationsmentioning
confidence: 99%
“…IL-10 is a pleiotropic cytokine, and a wealth of evidence supports its regulatory role in the pathology process of several kinds of diseases (Alvarado-Arnez et al, 2015;Ghaleh Baghi et al, 2015;Hsu et al, 2015;Khodaeian et al, 2015). In addition, experimental studies indicated that IL-10 expression could maintain the balance between proinflammatory and anti-inflammatory stimuli in the process of cerebrovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…The gene encoding IL-10 (IL10) is present on the chromosomal locus 1q31-32, and several genome regions of chromosome 1 (1q21-23, 1q31-32 and 1q42-44) have been observed to be correlated with development of several kinds of diseases, such as diabetes mellitus, peptic ulcer disease, coronary artery disease, leprosy, chronic hepatitis B infection, and oral cancer (Alvarado-Arnez et al, 2015;Ghaleh Baghi et al, 2015;Hsu et al, 2015;Khodaeian et al, 2015;Miftahussurur and Yamaoka, 2015;Yang et al, 2015). The authors of previous researches have reported the correlation of IL10 gene polymorphisms with the ischemic stroke risk; however, the results are inconsistent (Munshi et al, 2010;Sultana et al, 2011;Xie et al, 2013;Qi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%